VARIASI GENETIK SUKU BATAK YANG TINGGAL DI KOTA DENPASAR DAN KABUPATEN BADUNG BERDASARKAN TIGA LOKUS MIKROSATELIT DNA AUTOSOM - UNADI, YOSSY CAROLINA; NARAYANI, INNA; JUNITHA, I KETUT (Jurnal Biologi Udayana; Vol 14 No 2 (2010): Jurnal Biologi, 2010)
Study of genetic variation on three microsatellite DNA loci D2S1338, D13S317 and D16S539 from 76 unrelated individuals of Batak ethnic who live in Denpasar city and Badung regency were analyzed by using PCR method (SuperMix Kit, Invitrogen). DNA samples were extracted from blood cell using phenol-chloroform method and ethanol precipitation. The result of this study found 14 alleles on D2S1338 locus, 10 alleles on D13S317 locus and eight alleles on D16S539 locus. The finding showed high genetic diversity on three loci as well as on three sub-ethnic Batak of Batak Toba, Karo and Simalungun which were 0.8637; 0.7314 and 0.7692 respectively.
Keywords: DNA microsatellite; Batak ethnic; genetic variation; allele frequency; heterozygosity